Efektivitas Konseling Kelompok Dengan Teknik Self Management Untuk Mereduksi Anxiety (Kecemasan) Dalam Komunikasi Interpersonal Remaja Di Panti Asuhan Aisyiyah Humairah Palembang - Febrianti, Zona; Marianti, Lena; Suryati, Suryati (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2023)
Abstract: The background of this research is that teenagers often remain silent when asked to explain and if they are appointed to be event officials they choose to hide so as not to be chosen and even push and point at each other with other teenagers. The responses given by teenagers were feeling afraid, anxious, and breaking out in cold sweat. This research examines the effectiveness of group counseling on self-management techniques to reduce interpersonal communication anxiety among teenagers at the Aisyiyah Humairah orphanage in Palembang. The aim of the research is to determine the level of interpersonal communication anxiety among adolescents before implementing self-management techniques, and to determine the effectiveness of self-management technique group counseling to reduce interpersonal communication anxiety among adolescents at the Aisyiyah Humairah Orphanage in Palembang. This research uses quantitative research methodology and experimental research type. The results of the research showed that firstly, the TSR test (high, medium, low) showed that the interpersonal communication anxiety level of teenagers increased (high) by a percentage of 75.85% after group counseling with self-management techniques for teenage anxiety decreased to 61.28%. Second, it is known from the Wilxocon test results obtained by Asymp.sig (2-tailed) with a value of 0.002. Value 0.002.